A Note on the Great Persecution in the West - Frend, W. H. C. (Studies in church history, 1965)
The Great Persecution in the Western provinces of the Roman Empire was relatively short and sharp. Eusebius in both his Ecclesiastical History and the Martyrs of Palestine contrasts the eight long years of repression suffered by the East, first under Diocletian and Galerius and then under Maximian, with the persecution of ‘scarcely two years’ duration’ endured by the Western Christians. In the West, indeed, the persecution of Valerian 257-60 seems to have been longer and perhaps more costly in human lives, and that of Decius more dangerous to the Church.